Oxytocin receptor gene (OXTR) DNA methylation is associated with autism and related social traits – A systematic review. (July 2021) - Moerkerke, Matthijs; Bonte, Marie-Laure; Daniels, Nicky; Chubar, Viktoria; Alaerts, Kaat; Steyaert, Jean; Boets, Bart
Graphical abstract: OXTR is a single copy, located on chromosome 3 (hg38, 3:8750408-8769628). The gene contains 3 introns and 4 exons. This figure shows the structure of OXTR with the approximate location of the CpG sites -860, -901, -924, -934, -959, -982, -989 (upstream from the translation start site) and the rs53576 SNP. The red lines indicate the investigated CpG sites/regions and the green lines show studies investigating the SNP rs53576 as well, for the included studies in this review: 1. (Gregory et al., 2009), 1A: exons 1-3, introns 1 (sites -860; -901;-924; -934; -959) and 2, and 1B. intron 3; 2. (Elagoz Yuksel et al., 2016), exon 1-3 and intron 1 and 2; 3. (Andari et al., 2020), intron 1 (site -989); 4. (Siu et al., 2021), intron 1 (site -982); 5. (Jack et al., 2012), intron 1 (site -934); 6. (Puglia et al., 2015), intron 1 (site -934); 7. (Rijlaarsdam et al., 2017), exon 2 (average of 3 sites); 8. (Puglia et al., 2018), intron 1 (site -934); 9. (Chen et al., 2019), intron 1 (sites -934, -924 and -901); 10. (Krol et al., 2019), intron 1 (site -924); 11. (Chagnon et al., 2015), exon 3; 12. (Ziegler et al., 2015), exon 3 (average over 12 sites). * The arrows schematically show OXTR hyper- (↑) or hypomethylation (↓) in ASD or in association with autism traits, social perception/cognition or social anxiety per study. Highlights: OXTR hypermethylation is associated with higher quantitative autism traits in adults. OXTR hypermethylation is associated with increased brain activity while performing social tasks (indicating a higher need for resources). OXTR hypermethylation is associated with decreased functional brain connectivity. Contradictory, OXTR hypomethylation was found in children with ASD and was also associated with more social anxiety. Abstract: There is emerging evidence implicating oxytocin receptor gene ( OXTR ) DNA methylation (DNAm) in social behaviour. This review investigated its association with autism spectrum disorder (ASD) characteristics and related social dimensions, both in individuals with and without ASD. Twelve articles investigating OXTR DNAm in relation to ASD, social perception/cognition and social anxiety were included. We found that hypermethylation is associated with (i) higher quantitative autism traits in adults, reflecting a higher incidence of autism characteristics, (ii) increased brain activity while performing social tasks (indicating a higher need for resources) and (iii) decreased functional connectivity. (iv) Contradictory, hypomethylation was found to be present in children (especially boys) with ASD and was also associated with more social anxiety. While the included studies displayed a large variability, for example in terms of population characteristics, analysed OXTR DNAm regions, and adopted scales/questionnaires, an initial developmental pattern of results emerged, suggesting an association between hypermethylation of OXTR and autism traits in adults. Nonetheless, future studies are warranted to corroborate these initial conclusions.